PEMBELAJARAN MENULIS RESENSI BERDASARKAN KURIKULUM 2013 PADA SISWA KELAS X SMK NEGERI 3 PONTIANAK - Siti Nurjanah; Nanang Heryana; Syambasril Syambasril (Universitas Tanjungpura, 2019)
AbstractThe background of this research is Indonesia language learning in 2013 Curriculum is text-based learning. Learning to write reviews is text-based learning carried out by Indonesian language subject teachers in class X of SMK Negeri 3 Pontianak. In this learning there are still obstacles such as the difficulty of students in expressing their own ideas. The method used in this research is descriptive method. The form of research used is qualitative. The aim is to find out whether the teacher has applied learning to write reviews based on the 2013 curriculum in terms of planning, implementation, and evaluation in the teaching-learning process. Data collection is done through observation, and documentation. The results of the data analysis show that the lesson plan (RPP) formulated by the teacher in the first, second, and third meeting in learning to write a review reflects the 2013 curriculum-based learning although there are still shortcomings in formulating indicators. The implementation of learning at the first, second, and third meeting consisted of preliminary, core and concluding activities carried out in accordance with the 2013 curriculum. The evaluation of learning done by the teacher is good by using instruments to assess attitudes, knowledge, and abilities.Keywords: Learning, Writing Reviews, 2013 Curriculum